Are There Postnatal Benefits to Prenatal Kick Counting? A Quasi-Experimental Longitudinal Study - Owens, Brenna; Libertus, Klaus (Frontiers in Psychology, 2022)
Mild signs of postpartum depression or anxiety are present in up to half of all new mothers. However, the impact of having the “baby blues” on infant development remains largely unknown. The current study explores a potential relation between mother’s self-reported depression or anxiety symptoms and infant’s motor development in a longitudinal sample of 50 mother-infant dyads. Further, we examine whether engaging in fetal kick counting during pregnancy may reduce maternal psychopathology symptoms and thereby positively influence infant motor development and parent-child engagement during the first months of life. We hypothesized that subclinical maternal psychopathology would negatively impact infant motor development, and that completing a fetal kick count activity during the third trimester would reduce overall signs of maternal psychopathology. Results only partially support these hypotheses. Postpartum maternal anxiety seems to negatively affect the emergence of infants’ fine motor skills. However, engaging in fetal kick counting during pregnancy did not reduce maternal depression or anxiety symptoms. Nevertheless, preliminary evidence suggests that engaging in fetal kick counting may impact early child development by altering the mother’s attitudes towards the child. Future research is needed to examine the value of this low-cost intervention strategy more closely.